Hemin-doped metal–organic frameworks based nanozyme electrochemical sensor with high stability and sensitivity for dopamine detection. Issue 4 (11th January 2021) - Kang, Kai; Wang, Beibei; Ji, Xueping; Liu, Yuheng; Zhao, Wenrui; Du, Yaqing; Guo, Zhiyong; Ren, Jujie
Abstract : Hemin-doped-HKUST-1 nanozyme has been successfully synthesized and used for dopamine detection with excellent reproducibility, stability and anti-interference. Abstract : This study reports a new type of artificial nanozyme based on Hemin-doped-HKUST-1 (HKUST-1, also referred to as MOF-199; a face-centered-cubic MOF containing nanochannels) as a redox mediator for the detection of dopamine (DA). Hemin-doped-HKUST-1 was successfully synthesized by one-pot hydrothermal method, which was combined with reduced graphene oxide (rGO) modified on a glassy carbon electrode (GCE) to construct a sensor (Hemin-doped HKUST-1/rGO/GCE). The morphology and structure of Hemin-doped-HKUST-1 were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM) and infrared spectra (IR) techniques. The Hemin-doped HKUST-1/rGO nanozyme showed an excellent electrocatalytic activity for DA oxidation, which is due to the enhanced Hemin activity through the formation of a metal–organic framework (MOFs) and the synergy between the Hemin-doped HKUST-1 and rGO in nanozyme. The resulted sensor exhibited a high sensitivity of 1.224 μA μM −1, with a lower detection limit of 3.27 × 10 −8 M (S/N = 3) and a wide linear range of 0.03–10 μM for DA detection. In addition, due to the stabilizing effect of MOFs on heme, the sensor showed satisfactory stability and has been successfully applied to the detection of DA in serum samples, indicating that this work has potential value in clinical work.